Avaliação in vitro da citotoxicidade, genotoxicidade e mutagenicidade de materiais estéticos de preenchimento facial - Borghetti, Ruchielli Loureiro (2015)
Hyaluronic acid (HA) and polymethylmethacrylate (PMMA) are the most used dermal fillers nowadays. The indiscriminate use of such substances has brought to light unwanted adverse effects. Thus biocompatibility studies are a necessity, since the scientific literature does not clarify the etiology of these effects. The current research has evaluated cytotoxic, genotoxic and mutagenic responses from distinct in vitro tests performed in an independent manner. The cytotoxicity potential of the materials was evaluated by the induction of an inhibition halo in a solid yeast cultures. To conduce a preliminary view, the dilutions ranging from 10-2 to 10-5 were verified. For quantitative test, the colonies were counted to estimate the CFU/mL (colony-forming units per milliliter) values. Halo inhibition test showed that only silicone, used as a positive control, was capable of inducing cytotoxicity in this yeast. The preliminary experiment also indicated silicone and HA 16 mg/mL as a cellular toxicity inductor material. Quantitative test indicated that HA 20 mg/mL and 0.1mL volume inhibited cell proliferation (ANOVA, Tukey test, p≤ 0.05). PMMA was dosedependent to 2 and 10% concentrations (Tukey test, p≤ 0.05). 30% PMMA showed cell proliferation inhibition similar to the negative control. Silicone proved to inhibit S. cerevisiae cell proliferation (Tukey test, p≤ 0.05). In a second investigation, in Chinese hamster lung fibroblasts (V79 cells), the cytotoxic, genotoxic and mutagenic potentials of 20 mg/mL HA and 30% PMMA were determined. For testing these effects, clonogenic survival, comet and micronucleus assay were performed. HA and PMMA were able to decrease the colony formation when cultures were exposed to compounds by 24 h followed by 6 days in drug-free media. In addition, no genotoxic effects were detected in the 3 or 24 h of exposure to HA or PMMA. In the same manner, both dermal fillers did not induce increase in the micronucleus frequency in binucleated cells. Taken together, these results suggest that (1) 20 mg/mL HA and 10% PMMA are cytotoxicity inductors for the eukaryotic model S. cerevisiae; (2) 20 mg/mL HA and 30% PMMA have a weak cytotoxic activity in V79 cells; (3) the tested substances do not cause detectable DNA damage and chromosome alterations in V79 cells.